2014
DOI: 10.1007/s10689-014-9759-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of risk-reducing surgery in unaffected women at increased familial risk of breast and/or ovarian cancer

Abstract: Purpose: To prospectively investigate long-term psychosocial outcomes for women who opted for risk-reducing mastectomy (RRM) and/or risk-reducing salpingo-oophorectomy (RRSO).Methods: Unaffected women from high-risk breast cancer families who had completed baseline questionnaires for an existing study and subsequently underwent RRM and/or RRSO, completed measures of perceived breast and ovarian cancer risk, anxiety, depression, cancer-related anxiety, body image, sexual functioning, menopausal symptoms, use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Studies included both BRCA1 and 2 carriers, except for 2, which included only BRCA1 carriers [21, 31]. In addition to BRCA mutation carriers, 6 studies included women who had high risk of breast and ovarian cancer with no confirmed genetic diagnosis [29, 3236]. Other variables, such as time since RRSO, body mass index (BMI), smoking status, history of breast cancer and hysterectomy were reported in some but not all studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies included both BRCA1 and 2 carriers, except for 2, which included only BRCA1 carriers [21, 31]. In addition to BRCA mutation carriers, 6 studies included women who had high risk of breast and ovarian cancer with no confirmed genetic diagnosis [29, 3236]. Other variables, such as time since RRSO, body mass index (BMI), smoking status, history of breast cancer and hysterectomy were reported in some but not all studies.…”
Section: Resultsmentioning
confidence: 99%
“…ET >0.05Vasomotor symptomsChallberg [33]FACT-ES j 141-Hot flashes OR = 0.55(0.23-1.28) f >0.05NANight sweats OR = 0.28(0.11-0.76) f <0.05 Finch [38]Self-reported73-Hot flashes OR = 0.27(0.09-0.80) f 0.03 13.6 months (10.8–21.8)Madalinska [34]FACT-ES j 164-Hot flashes OR = 0.34(0.17-0.70) f <0.01 NANight sweats OR = 0.51(0.26-1.00) f 0.04 Sexual functionFinch k [38]SAQ d 61Pleasure = 1.220.5013.6 months (10.8–21.8)Discomfort = 1.92 0.03 Habit = 0.190.10Heiniger [29]SAQ d 38NS for all 3 dimensions->0.05Johansen [36]SAQ l 157Pleasure systemic HT (both ET and EPT) = 0.9->0.05102Pleasure local HT = -1.5->0.05116Pleasure systemic ET = 0.8>0.05111Pleasure systemic EPT = 0.5>0.05112Pleasure systemic tibolone = 1.5>0.05157Discomfort systemic HT (both ET and EPT) = -1.2 <0.01 102Discomfort local HT = -0.70.2116Discomfort systemic ET = -1.1 0.04 111Discomfort systemic EPT = -1.2 0.02 112Discomfort systemic tibolone = -1.39 <0.01 Madalinska [34]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations